MORPHOLOGICAL DEVIATIONS PRODUCED BY INDONESIAN ADOLESCENT DYSLEXIC READERS - Angkita Wasito Kirana; Masitha Achmad Syukri; Deny Arnos Kwary (Linguistik Indonesia, 2020)
Even though the major problem of dyslexic readers is in their phonological awareness, morphological complexity of a language might also affect their performance in reading, especially for language with transparent orthography like the Indonesian language. This study aims to find the patterns of morphological deviations produced by Indonesian dyslexic adolescents during a reading activity.  In this study, a set of instrument consisting of 160 words that were chosen based on their morphological complexity is prepared. The words were then combined into 55 sentences which then were asked to be read aloud by the participants. The result of morphological deviations indicated that the deviations occured equally frequent both in inflectional and derivational affixes. Most of the morphological deviation (i.e. 96%) occured in polymorphemic words. In addition, participants tend to simplify the polymorphemic words by omitting the affixes and reading only the root instead. At least 58% of the deviations were affix ommision. This means teachers of dyslexic readers need to provide more training on polymorphemic words, particularly those that have affixes.